Acute Toxicity Test of Laundry Detergent Waste and Sublethal Test to Gourami Fingerlings (Osphronemus gouramy) - Rizky Ramadhan; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Perikanan dan Kelautan, 2023)
Laundry detergent waste is toxic and can harm the environment and aquatic life. This study aims to find out the effect of detergent waste on the growth and mortality of gourami (Osphronemus gouramy) seeds and the threshold value of laundry detergent waste that can still be tolerated by gourami seeds. This research was carried out from December 2020 to January 2021 at the Aquaculture Environmental Quality Laboratory, Faculty of Fisheries and Marine Science (FPK) University of Riau. This research method used an experimental method using a completely randomized design (CRD) method with three tests namely the preliminary test, acute toxicity test, and sublethal test. Observation of fish behavior and morphology during the test is described descriptively. In the preliminary test, the lower and upper threshold values were 10 mlL-1and 100 mlL-1. Then in the acute toxicity test, the value LC50-96hour was obtained at 30.1 mlL-1with a biological safe limit value of 0.301 mlL-1. The best treatment obtained from the sublethal test was P1 with a concentration of 0.3 mlL-1resulting in an absolute weight gain of 1.03 g, a specific growth rate of 1.56%, and a survival rate of 83.33%. The mortality rate is influenced by the concentration of detergent waste, the higher the concentration of detergent waste, the higher the mortality rate. Detergent waste that enters the waters affects the surface tension of the water so that the oxygen diffusion process is hampered, the reduced dissolved oxygen stresses the fish. Detergent waste can also enter the fish's body, irritating the gills and other organs, which can lead to death